Persistently high wealth inequality in Germany - Markus M. Grabka; Christian Westermeier (DIW Economic Bulletin, 2014)
According to current analyses based on the Socio-Economic Panel Study (SOEP), the total net assets of German households in 2012 amounted to 6.3 trillion euros. Almost 28 percent of the adult population had no or even negative net wealth. On average, individual net assets in 2012 totaled over 83,000 euros, slightly more than ten years previously. The degree of wealth inequality also remained virtually unchanged. With a Gini coefficient of 0.78, Germany has a high degree of wealth inequality compared to other countries, and there is still a wide gap between western and eastern Germany almost 25 years after unification. In 2012, the average net wealth of eastern Germans was less than half that of western Germans.
Keywords: D31; I31; 330; wealth inequality; wealth portfolio; SOEP